Back and neck pain and poor sleep quality in adolescents are associated even after controlling for confounding factors: An epidemiological study - Scarabottolo, Catarina Covolo [UNESP]; Pinto, Rafael Zambelli; Oliveira, Crystian Bitencourt [UNESP]; Tebar, William Rodrigues [UNESP]; Saraiva, Bruna Thamyres Ciccotti [UNESP]; Morelhão, Priscila Kalil [UNESP]; Dragueta, Leandro Delfino [UNESP]; Druzian, Gustavo Santos [UNESP]; Christofaro, Diego Giulliano Destro [UNESP] (My University, 2020)
Objective: Back pain and poor sleep quality are public health issues. Relating to adolescents particularly, the way in which this relationship can occur is still unclear. The aim of this study was to investigate whether low back and neck pain are associated with sleep quality among adolescents. Material and Methods: In total, 1011 randomly selected adolescents participated in this study. Neck and back pain were assessed using the Nordic questionnaire, while sleep quality was assessed through the Mini-Sleep Questionnaire. The confounding variables used in the statistical analysis were age, socioeconomic status, physical activity, and body mass index. To analyze the associations between sleep quality and low back and neck pain, multivariate models and binary logistic regression were used. Results: 19.9% of the girls reported low back pain while 18.9% reported neck pain. 15.6% of the boys reported low back or neck pain. Regarding low sleep quality, the prevalence was 46.0% for girls and 49.6% for boys. An association was observed between low back pain and sleep quality among girls (OR=1.98 [1.25 - 3.12]) and boys (OR=2.58 [1.48 - 4.50]). An association between neck pain and sleep quality was also observed among girls (OR=2.27 [1.41 - 3.64]) and boys (OR=2.80 [1.59 - 4.91]). Conclusion: Low back pain and neck pain were associated with poor sleep quality among adolescents even after the insertion of confounding variables.
Keywords: Adolescent; Back Pain; Sleeplessness; Students